Adaptive Regional Innovation Systems: Addressing Latin America's Challenges - Silvio Cario; Rafaela Burger; Dannyela Lemos; Pablo Bittencourt (Journal of Technology Management & Innovation, 2023)
This study aims to present the definition and characteristics of regional innovation systems as well as actions focused on their development. For this purpose, the present study uses the neo-Schumpeterian theoretical bibliography as support for the analysis. The conclusions point out that in the Brazilian territory, companies, universities, research institutes, government institutions, among other actors, develop interactive and cooperative relationships that enable innovative development. In this field, there are habits, values, cultures, and their own productive and institutional structures that enable different patterns of regional innovation systems. It is up to the State to play the role of promoter of regional development, given its capacity to mediate interaction, deliver political articulation, and foster innovation programs. Development policies aimed at interaction and cooperation, learning processes, the formation of joint strategies, and the availability of resources are highlighted.